Early Perihematomal Edema Expansion: Definition, Significance, and Association with Outcomes after Intracerebral Hemorrhage. (13th September 2021) - Lv, Xin-Ni; Li, Zuo-Qiao; Deng, Lan; Yang, Wen-Song; Li, Yu-Lun; Huang, Yuan-Jun; Shen, Yi-Qing; Xie, Xiong-Fei; Li, Xin-Hui; Wang, Zi-Jie; Zhang, Zhi-Wei; Lv, Fa-Jin; et al.
Abstract : Objective . To investigate the association between early perihematomal edema (PHE) expansion and functional outcome in patients with intracerebral hemorrhage (ICH). Methods . Patients with ICH who underwent initial computed tomography (CT) scans within 6 hours after the onset of symptoms and follow-up CT scans within 24 ± 12 hours were included. Absolute PHE increase was defined as the absolute increase in PHE volume from baseline to 24 hours. A receiver-operating characteristic (ROC) curve was generated to determine the cutoff value for early PHE expansion, which was operationally defined as an absolute increase in PHE volume of >6 mL. The outcome of interest was 3-month poor outcome defined as modified Rankin scale score of ≥4. A multivariable logistic regression procedure was used to assess the association between early PHE expansion and outcome after ICH. Results . In 233 patients with ICH, 89 (38.2%) patients had poor outcome at 3-month follow-up. Early PHE expansion was observed in 56 of 233 (24.0%) patients. Patients with early PHE expansion were more likely to have poor functional outcome than those without (43.8% vs. 11.8%, p < 0.001 ). After adjusting for age, admission systolic blood pressure, admission Glasgow Coma Scale score, baseline ICH volume and the presence of intraventricular hemorrhage, and time from onset to CT, early PHE expansion was associated with poor outcome (adjusted odds ratio, 4.25; 95% confidence interval, 1.70–10.60; p = 0.002 ). Conclusions . The early PHE expansion was not uncommon in patients with ICH and was correlated with poor outcome following ICH.